SIMULASI PhET: SEBUAH STUDI DESKRIPTIF KUALITATIF TERHADAP KETERAMPILAN ARGUMENTASI - Wulandari, Arum (Badan Perencanaan Pembangunan Daerah dan Penelitian dan Pengembangan Kabupaten Wonogiri, 2024)
This study aims to explore students' argumentation skills in physics learning using PhET simulation as a teaching medium. The research method used is qualitative descriptive, with data collection through observation, interviews, and document analysis. The subjects of this study were 10th-grade high school students. The results show that using PhET simulation improves students' argumentation skills. These argumentation skills develop through discussions and problem-solving facilitated by the simulation. This study concludes that PhET simulation can be an effective tool in physics learning to enhance students' critical thinking and argumentation skills.